PET/CT in cancer : an interdisciplinary approach to individualized imaging - Beheshti, Mohsen; Langsteger, Werner; Rezaee, Alireza (Elsevier, 2018)
Edited, authored, and reviewed by an expert team of oncologists and nuclear physicians/radiologists, this one-of-a-kind title helps you make the most of the critical role PET/CT plays in cancer staging and therapeutic responses to individualized treatments. Drs. Mohsen Beheshti, Werner Langsteger, and Alireza Rezaee place an emphasis on cutting-edge research and evidence-based practice, ensuring that you're up to date with every aspect of this fast-changing field. For each tumor entity, you'll find authoritative discussions of background, pathology, common pattern of spread, TNM classification, clinical guidelines, discussion, evidence-based recommendations, key points, and pitfalls.